Model Pentahelix dalam Pengembangan Usaha Mikro, Kecil dan Menengah (UMKM) Manggarsari - Beatrice, Cleodora; Hertati, Diana (Universitas Dr. Soetomo Surabaya, 2023)
This study aims to know and describe the pentahelix model in the development of MSMEs Manggarsari, Tambaksari District, Surabaya City. Micro, Small and Medium Enterprises (MSMEs) are an important part of the economy in Indonesia, especially in the city of Surabaya, marked by their large contribution to the economy and reducing unemployment by absorbing labor. MSME development needs to be carried out to support MSMEs in improving and growing competitive capabilities. In realizing development for MSMEs, the involvement of various actors will help development run optimally. Through synergy in the pentahelix, namely cooperation between stakeholders consisting of academy, business, government, community, and media (ABCGM) in developing innovation and economy. The method used in this study is descriptive qualitative. The data collection techniques in research are through interviews, documentation, and literature studies. The results showed that in the development of MSMEs Manggarsari, Tambaksari District, Surabaya City, the five actors in the pentahelix model have been involved, namely academics, business, community, government, and media. Although in its implementation, there are obstacles in carrying out its role.